A Heating Mechanism via Magnetic Pumping in the Intracluster Medium - Francisco Ley; Ellen G. Zweibel; Mario Riquelme; Lorenzo Sironi; Drake Miller; Aaron Tran (The Astrophysical Journal, 2023)
Turbulence driven by active galactic nuclei activity, cluster mergers, and galaxy motion constitutes an attractive energy source for heating the intracluster medium (ICM). How this energy dissipates into the ICM plasma remains unclear, given its low collisionality and high magnetization (precluding viscous heating by Coulomb processes). Kunz et al. proposed a viable heating mechanism based on the anisotropy of the plasma pressure under ICM conditions. The present paper builds upon that work and shows that particles can be heated by large-scale turbulent fluctuations via magnetic pumping. We study how the anisotropy evolves under a range of forcing frequencies, what waves and instabilities are generated, and demonstrate that the particle distribution function acquires a high-energy tail. For this, we perform particle-in-cell simulations where we periodically vary the mean magnetic field B ( t ). When B ( t ) grows (dwindles), a pressure anisotropy P _⊥ > P _∥ ( P _⊥ < P _∥ ) builds up ( P _⊥ and P _∥ are, respectively, the pressures perpendicular and parallel to B ( t )). These pressure anisotropies excite mirror ( P _⊥ > P _∥ ) and oblique firehose ( P _∥ > P _⊥ ) instabilities, which trap and scatter the particles, limiting the anisotropy, and providing a channel to heat the plasma. The efficiency of this mechanism depends on the frequency of the large-scale turbulent fluctuations and the efficiency of the scattering the instabilities provide in their nonlinear stage. We provide a simplified analytical heating model that captures the phenomenology involved. Our results show that this process can be relevant in dissipating and distributing turbulent energy at kinetic scales in the ICM.